Workshop dan Bimbingan Teknis Tata Cara Perencanaan serta Penganggaran Aktivitas Penggunaan Dana Desa - Dwi Indah Lestari; Muhammad Ridwan Mustafa; Muhammad Anggionaldi (Universitas Mathla'ul Anwar Banten, 2020)
WORKSHOP AND TECHNICAL ASSISTANCE PLANNING AND BUDGETING OF VILLAGE FUND. The purpose of this technical assistance was to enhance the skill of village government officers in Desa Tanimulya. The project was divided into 4 focus that consists of: workshop, review long term plan and short term plan, introduce enterprise owned by the village and manual procedure design for several main activities. This project was held in Tanimulya. There were 30 participants in this activity including head of the village and his staff. After the technical assistance has done, it can be seen that the village officer in Tanimulya understood the relation between long term planning and short term planning thus, it makes them easier to calculate the budget for each activitiy inside the plan.